2021
DOI: 10.3390/plants10030490
|View full text |Cite
|
Sign up to set email alerts
|

Biotic and Abiotic Elicitors of Stilbenes Production in Vitis vinifera L. Cell Culture

Abstract: The in vitro cell cultures derived from the grapevine (Vitis vinifera L.) have been used for the production of stilbenes treated with different biotic and abiotic elicitors. The red-grape cultivar Váh has been elicited by natural cellulose from Trichoderma viride, the cell wall homogenate from Fusarium oxysporum and synthetic jasmonates. The sodium-orthovanadate, known as an inhibitor of hypersensitive necrotic response in treated plant cells able to enhance production and release of secondary metabolite into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 84 publications
2
7
0
Order By: Relevance
“…Generally, the application of elicitors caused the colour changes of the cell cultures from green to brown, due to the endogenously increased overproduction of hydrogen peroxide after elicitation 26 . Browning in callus cultures is accompanied by the activation of the oxidative phenolic metabolism 27 . It has been observed in our study that brown cell cultures produced a higher amount of metabolites of artemisinin and the phenolic (quercertin and caffeic acid) pathway.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…Generally, the application of elicitors caused the colour changes of the cell cultures from green to brown, due to the endogenously increased overproduction of hydrogen peroxide after elicitation 26 . Browning in callus cultures is accompanied by the activation of the oxidative phenolic metabolism 27 . It has been observed in our study that brown cell cultures produced a higher amount of metabolites of artemisinin and the phenolic (quercertin and caffeic acid) pathway.…”
Section: Resultssupporting
confidence: 54%
“…26 Browning in callus cultures is accompanied by the activation of the oxidative phenolic metabolism. 27 It has been observed in our study that brown cell cultures produced a higher amount of metabolites of artemisinin and the phenolic (quercertin and caffeic acid) pathway. Taranto et al 28 also found that callus browning is caused by polyphenolic compounds present when the explants were wounded.…”
Section: Influence Of Elicitors On Callus Formation and Morphological...mentioning
confidence: 47%
“…Jasmonates are considered widespread elicitors since they affect several signaling pathways stimulating the production of different classes of secondary metabolites in plants and microorganisms (Lourenço et al 2016 ). The more active derivative methyl jasmonate (MeJA) and the less active cis-jasmonate and dihydrojasmonic acid are the main plant stress compounds involved in the signaling of defense responses, primarily due to induction of genes involved in phytoalexin and phenolics biosynthesis (Sák et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we used calli from leaves of C. cardunculus ‘Spagnolo’ with the aim of evaluating the efficacy of two strategies of abiotic elicitation in stimulating the accumulation of bioactive metabolites, while having a minimal perturbation effect on the growth of cardoon cell cultures. Albeit cardoon is a tolerant species able to also grow in limiting conditions [ 16 , 45 , 46 , 47 ], in both whole plant and in the derived calli a common response to stress is represented by the decrease in growth [ 48 , 49 , 50 ] and this is a typical drawback in the use of synthetic biotic elicitors and to a lesser extent for abiotic elicitors [ 51 ]. In this work, alteration in the fresh weight of ‘Spagnolo’ calli was monitored during 6 °C chilling stress treatment for 7 or 14 days or NaCl (50, 100, or 150 mM) salt stress treatment for 14 or 28 days, observing a strong reduction of fresh weight in a dose and time-dependent manner in salt stressed calli.…”
Section: Discussionmentioning
confidence: 99%